2021
DOI: 10.1001/jamapsychiatry.2021.2880
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Resource Groups for Improving Empowerment, Quality of Life, and Functioning of People With Severe Mental Illness

Abstract: IMPORTANCEAlthough the importance of recovery-oriented care for people with severe mental illness (SMI) is widely acknowledged, essential elements such as personalization and involvement of significant others are not adequately implemented in practice.OBJECTIVE To determine whether using resource groups (RGs) within flexible assertive community treatment (FACT) has favorable effects on empowerment and recovery-related outcomes in people with SMI. DESIGN, SETTING, AND PARTICIPANTSThis assessor-blind, multisite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 71 publications
4
11
0
1
Order By: Relevance
“…In particular, social support by significant others, peers and trainers was highly valued and experienced as helpful. This is in line with a recently published study among 158 patients with a serious mental illness, which also showed that involving relatives and significant others in treatment facilitated the personal recovery process (39). As reported in previous research, our study also demonstrates that involving significant others can be challenging, e.g., because no significant other was available or participants did not want to involve them (40-42).…”
Section: Discussionsupporting
confidence: 93%
“…In particular, social support by significant others, peers and trainers was highly valued and experienced as helpful. This is in line with a recently published study among 158 patients with a serious mental illness, which also showed that involving relatives and significant others in treatment facilitated the personal recovery process (39). As reported in previous research, our study also demonstrates that involving significant others can be challenging, e.g., because no significant other was available or participants did not want to involve them (40-42).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, several papers describe the Resource Group methodology that also promotes citizenship because the main feature of this methodology is that ownership and direction lie with the client. Of the included studies, there were two RCTs ( 73 , 74 ) with positive results, one meta-analysis ( 71 ), one review ( 72 ), and one qualitative paper ( 75 ). Finally, we found some papers on self-reliance.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, a “resource group” involving care providers, parents, and other important relatives could help. A resource group is a network that can help better navigate critical transitions in life ( 37 ). Such a combination of informal and formal networks is already deployed within Adult Flexible ACT and is usually set up right at the start ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…A resource group is a network that can help better navigate critical transitions in life ( 37 ). Such a combination of informal and formal networks is already deployed within Adult Flexible ACT and is usually set up right at the start ( 37 ). Working with a resource group could ensure continuity of care and prevent the client from falling back on (specialized) mental health care services.…”
Section: Discussionmentioning
confidence: 99%